QUALITY ASPECTS OF LATVIAN HIGHER EDUCATION:COMPETENCE AND COOPERATION - Alīda Samuseviča (European Scientific Journal, ESJ, 2014)
This paper reviews current problems in Latvian higher education. It outlines the challenges that economic and social change presents to the pedagogical process of higher education by focusing on the topicality and significance of univeristy teachers‘ pedagogical competence and professional responsibility in sustaining a meaningful and productive intellectual dialogue with students. Findings from theoretical and empirical research inform the tensions of pedagogical interaction and cooperation that are identified in the study process and described in the present paper. Insights from relevant research are used to devise a system of characteristics and features of university teachers‘ pedagogical competence to sustain effective pedagogical interaction during the study process. Opportunities are inferred and pinpointed for improving pedagogical cooperation with a view to sustaining a more solid scientific, intellectual and professional dialogue in higher education, which is seen as amenable to infusions of insights from relevant research. Potential problematic issues are apprehended in the sphere of higher education pedagogy, which are pertinent to improving the effectiveness of pedagogical interaction and enabling universities to function more efficiently.